The beneficial effect of Pluchea lanceolata on aluminum chloride-induced Alzheimer's disease in rats - Asi̇rvatham, Raju; Pa, Daiay; Salam, Salwa (Hücresel Sinir Bilimleri ve Oksidatif Stres Derneği, 2022)
Aluminum chloride (AlCl3) causes neuroinflammation in rats, which leads to the development of Alzheimer's disease. The current study focused on the anti-Alzheimer and antioxidant potential of hydromethanolic extracts of Pluchea lanceolata (PL), a well-known Rasna source. Phytoconstituents such as pluchine and moretenol acetate are selected for the PASS online and molecular docking (in silico) experimental model. A total of 36 Wistar rats were divided into VI groups, each with six rats. Group I: normal control, Group II: disease control, Group III: Rivastigmine (0.3 mg/kg, p.o), Group IV and V: Hydromethanolic extract of PL (HMEPL, 200 mg/kg, 400 mg/kg, p.o), and Group VI: Ayurvedic Formulation of Rasna (AFR) (1ml/kg, p.o). Except for group I, all of the animals were given Aluminum Chloride (AlCl3) (300 mg/kg, p.o). AlCl3 and plant extracts were given for 20day treatment. On the 0th, 7th, 14th, and 20th days, the behavioural study and changes in body weight were evaluated. Rats were sacrificed on the 21st day, their brains were separated, and antioxidant enzyme levels, protein levels, and neurotransmitter levels were measured. Histopathologies of the cortex and hippocampus parts of the brain were studied. The number of entries, as well as time spent in the closed arm and time taken to ascend the pole, were all increased in Group II animals, but this was reversed in groups treated with 200 mg/kg, 400 mg/kg, and1 ml/kg dosages of HMEPL and AFR. In the disease control group, AlCl3 (300 mg/kg, p.o.) caused a 1.5 fold increase in protein content and 1.7 fold increase in malondialdehyde, similarly, 1.3 fold reduction in body weight, 2.2 fold superoxide dismutase, 3.3 fold catalase, and 3.1 fold glutathione level were observed and were corrected and restored in groups treated with HMEPL and AFR. Furthermore, the histopathology findings revealed that HMEPL and AFR provided the cellular-level protection. The active components of HMEPL were found to have anti-Alzheimer and antioxidant potential and were confirmed in an in silico investigation. HMEPL > AFR was the order of anti-Alzheimer and antioxidant effectiveness.
Keywords: Aluminum Chloride; Alzheimer; insilico; neurotransmitters; Pluchea lanceolata; Rasna; Toxicology; Toksikoloji; 3. Good health